(untitled) (Scientific journal of the Fergana State University, 2024)
The article analyzes the mystical essence of the concepts of reconciliation, peace, gratitude, harmony and discord, and reconciliation from a philosophical point of view. The role of these concepts in human improvement is justified in the views of Naqshbandi representatives.